Development of Raman gas analyzers at IMCES SB RAS - Petrov, Dmitry Vitalievich; Matrosov, Ivan I.; Kostenko, M. A.; Zaripov, Alexey R. (Atmospheric and oceanic optics)
Gas analyzers on the basis of Raman spectroscopy designed at the Institute of Monitoring of Climatic and Ecological Systems, Siberian Branch, Russian Academy of Sciences, are described. Their capabilities and advantages are shown in measurements of the composition of fuel gases (natural, bio-, and synthesis gases) and atmospheric and exhaled air. The features of the analyzer operation and the techniques for increasing the measurement accuracy are discussed.